2001
DOI: 10.3109/13506120108993820
|View full text |Cite
|
Sign up to set email alerts
|

Enhancedin vitroproduction of amyloid-like fibrils from mutant (S20G) islet amyloid polypeptide

Abstract: The amino acid substitution (S20G) is situated close to the region of the IAPP molecule implicated in the IAPP fibrillogenesis. The significantly increased formation of amyloid-like fibrils by IAPPS20G is highly interesting and may be associated with an increased islet amyloid formation in vivo and of fundamental importance in the pathogenesis of this specific form of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 30 publications
6
73
1
1
Order By: Relevance
“…S3 and Table S1), which agreed with the previous reports [16,17]. It is of interest to note that spectra showed modest differences in the region of 210-230 nm between the hIAPP and pIAPP fragments, where spectra of hIAPP (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and hIAPP (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) showed more positive CD signals than those of pIAPP (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and pIAPP (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) (Fig. 2A...…”
Section: Secondary Structures Determination By Far-uv CD and Spectra supporting
confidence: 89%
See 4 more Smart Citations
“…S3 and Table S1), which agreed with the previous reports [16,17]. It is of interest to note that spectra showed modest differences in the region of 210-230 nm between the hIAPP and pIAPP fragments, where spectra of hIAPP (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and hIAPP (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) showed more positive CD signals than those of pIAPP (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and pIAPP (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) (Fig. 2A...…”
Section: Secondary Structures Determination By Far-uv CD and Spectra supporting
confidence: 89%
“…Our results suggested that both 17D and 18R substitutions show minor impacts on the fibrillation of hIAPP (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). For hIAPP (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) carrying single 17D mutation or 17D18R double mutations, slightly lengthened lag times of 66.9 ± 12.9 min and 64.7 ± 17.5 min were observed as compared with the control hIAPP(17-29) (39.1 ± 10.0 min) ( Table 1). In contrast, 20R-hIA-PP(17-29) showed a dramatically prolonged lag time compared with hIAPP(17-29) (241.5 ± 114.0 min vs. 39.1 ± 10.0 min).…”
Section: Amyloid Formationmentioning
confidence: 58%
See 3 more Smart Citations